Engine revolution per minute estimation conversion for field experiment in farm mechanization training - Mohd Hudzari, Hj Razali; Wan Ishak, Wan Ismail; Mohd Rokli, Hizra Ramli; Abdul Aziz, Abdullah (2013)
In farm mechanization course, the most physical implement that will be used on primary application is the disc plough. The disc plough is the perfect tool when ploughing uneven ground that has obstacles and buried rocks. These ploughs have been specifically made to suit the tractors that used in filed application. This finding of this experiment suggests that the implement is easy to attach with tractor if specific procedures are followed. In this experiment, three disc ploughs were applied within the experiment and working width is 0.77m. Some basic calculation on field experiment is also presented